1991
DOI: 10.1104/pp.96.1.239
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Inhibitors Restore Nodulation to sym 5 Mutants of Pisum sativum L. cv Sparkle

Abstract: The sym 5 mutants of pea, Pisum sativum L. cv modulation. When Ag+ is added to the substrate from 4 days before to 4 days after inoculation with rhizobia, nodulation of sym 5 mutants is increased. The roots of the mutant need only be exposed to Ag+ for 4 hours to significantly increase nodule numbers. The content of free 1-aminocyclopropane-1-carboxylic acid and the production of ethylene in the lateral roots of sym 5 mutants do not differ from Sparkle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
2
3

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(45 citation statements)
references
References 19 publications
(18 reference statements)
3
37
2
3
Order By: Relevance
“…Both low temperature and Ag+ increased nodulation of the mutant. These results are similar to those reported previously (3,4).…”
Section: Methodssupporting
confidence: 93%
See 2 more Smart Citations
“…Both low temperature and Ag+ increased nodulation of the mutant. These results are similar to those reported previously (3,4).…”
Section: Methodssupporting
confidence: 93%
“…In addition, in the mutant, infection threads are seldom associated with cortical cell divisions. Nodulation of the mutant is enhanced by cool root temperature (which may lower ethylene production) and by Ag+ (an inhibitor of ethylene action) (3,4). However, we still lack direct evidence implicating ethylene in the inhibition of nodule primordium formation.…”
Section: Ag+ Treatmentmentioning
confidence: 96%
See 1 more Smart Citation
“…nigra ; Zaat et al, 1989) and soybean (Sugamuna et al, 1995 ;Ligero et al, 1999). Ethylene inhibitors significantly increased nodulation in alfalfa (Ligero et al, 1991 ;Caba et al, 1998) and in soybean (Ligero et al, 1999), even in the presence of inhibitory levels of nitrate, and restored nodulation in some pea nodulation mutants (Fearn & LaRue, 1991). It has also been suggested that endogenous ethylene provides positional information controlling the site where nodule primordia are formed (Heidstra et al, 1997).…”
Section: mentioning
confidence: 99%
“…Data on ethylene production or perception of such mutants are not known. Work by Fearn & LaRue (1991) has nonetheless shown that ethylene inhibitors partially restore nodulation to some of their pea nodulation (sym) mutants.…”
Section: mentioning
confidence: 99%